Optical properties of aerosols obtained from airborne lidar and several in-situ instruments during RACE - Strawbridge, K. B.; Li, S. M. (LIDAR ATMOSPHERIC MONITORING, 1997)
Two aircraft, the National Research Council of Canada (NRCC) Convair 580 (CV580) and NRCC DHC-6 Twin Otter, along with the Yarmouth and Digby Ferries, a ground site near Yarmouth and coordination with satellite overpasses (AVHRR and LANDSAT) provided an exceptionally well rounded compliment of observing platforms to meet the project objectives for the Radiation, Aerosols and Cloud Experiment (RACE) (refer to http://www.on.doe.ca/armp/RACE/ RACE.html for a complete list of instrumentation and investigators involved). The general flight plans involved upwind measurements of a selected target by the CV580 lidar, followed by coincident flights allowing the Twin Otter to perform in-site measurements while the Convair used a variety of remote sensors from above. The CV580 then descended to perform in-site measurements including size segregated samples through the use of a micro-orifice uniform deposit impactor (MOUDI). This paper will focus on the airborne lidar results during RACE and in particular introduce two case studies comparing the lidar with a MOUDI impactor and ASASP particle probe using Mie theory.